Digital Literacy and Reading Comprehension Achievement: A Correlation Study - Belingga, Firsta; Amalia, Shynta; Amrina, Rizqy Dwi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examined the correlation between digital literacy and reading comprehension among 99 fifth-semester pre-service teachers in the English Education Program at Universitas Islam Negeri Raden Fatah Palembang. Digital literacy involves using digital technologies to access and evaluate information, while reading comprehension focuses on understanding texts. Data were collected through a questionnaire and a test, then analyzed using descriptive statistics, Pearson correlation, and regression analysis. Results showed participants had good digital literacy but fair reading comprehension, with a very low, non-significant correlation between the two.